(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Patents are proprietary ownership privileges of intangible mental inventions. This paper studies the Patent system and the Indian Pharmaceutical Industry. In this we studied the pharmaceutical industry on patents, Indian pharmaceutical companies, patent regime in India, patents work differently in different industries, pharmaceutical patents problems, patents and research and development in developing countries and effect of product patents on the Indian pharmaceutical industry and patents.